Impact of COVID-19 Pandemic to the construction cost in Malaysia: construction stakeholder's perspective / Noor Anisah Abdullah ... [et al.] - Abdullah, Noor Anisah; Mohd Kamar, Izatul Farrita; Abdullah, Mohd Nazri; Mustapa, Nor Atiqah; Ahmad, Asmalia Che; Syed Mustafa, Syed Abdul Haris (2022)
World Health Organisation (WHO) has declared COVID-19 as a pandemic, which has forced most countries to an enforced lockdown. The COVID-19 has resulted in a widespread economic depression which forces many businesses across various sectors to shut down including the construction sector. As the government of Malaysia enforced a Movement Control Order (MCO) to break the chain of COVID-19, the construction sector with no exception has to bear with many problems that arise. It gives a huge impact on the ongoing project in the construction sector. Construction stakeholders are dealing with some difficulties as construction costs continue to increase as a result of workplace safety and health regulations, project suspension and termination, and productivity loss. Therefore, this paper aims to investigate the impact of COVID-19 on the construction cost in Malaysia from the perspective of construction stakeholder. The study employed a qualitative method that involves interview sessions through the Google Meet platform. 10 respondents from various backgrounds in the construction industry were involved in the interviews. The interviews offered information on their experience with the pandemic which mainly focused on the cost impact of the ongoing project in Klang Valley. All data are analysed using an atlas.ti software. The result reveals that the total cost of project, contract duration, increment of material price, additional temporary accommodation for labour and labour cost increment have an impact on the construction costing in Malaysia. These findings can raise awareness among the construction stakeholder on the impact of the pandemic outbreaks on the construction costing and help them to sustain the economic growth.